Firm Value Determinants in Chemical Sub-sector: Moderation by Firm Size (2017-2021): Faktor-faktor Penentu Nilai Perusahaan pada Sub-sektor Kimia: Moderasi oleh Ukuran Perusahaan (2017-2021) - Safitri, Anik; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study investigates the influence of tax planning, profitability, liquidity, and dividend policy on firm value in the chemical sub-sector manufacturing companies listed on the IDX during 2017-2021. Employing Partial Least Square (PLS) analysis on a sample of 50 companies selected through purposive sampling, we found that tax planning and profitability significantly impact firm value, while liquidity and dividend policy exhibit no such effect. Additionally, firm size moderates the relationship between tax planning and dividend policy with firm value but does not moderate the relationship between liquidity and profitability with firm value. These findings provide insights for policymakers and practitioners regarding the significance of tax planning strategies and the interplay between firm size and key determinants of firm value within the chemical manufacturing sector Highlights : Tax planning and profitability significantly influence firm value in the chemical manufacturing sector. Firm size moderates the relationship between tax planning and dividend policy with firm value. Liquidity and dividend policy show no significant effect on firm value in the chemical manufacturing sector. Keywords: Tax Planning, Firm Value, Partial Least Square (PLS), Chemical Manufacturing Sector, Firm Size Moderation